2022
DOI: 10.1063/5.0077483
|View full text |Cite
|
Sign up to set email alerts
|

A fast Tikhonov regularization method based on homotopic mapping for electrical resistance tomography

Abstract: Electrical resistance tomography (ERT) is considered a novel sensing technique for monitoring conductivity distribution. Image reconstruction of ERT is an ill-posed inverse problem. In this paper, an improved regularization reconstruction method is presented to solve this issue. We adopted homotopic mapping to choose the regularization parameter of the iterative Tikhonov algorithm. The standard normal distribution function was used to continuously adjust the regularization parameter. Subsequently, the resultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In [127], the prior regularization filter was modified to incorporate a priori knowledge of lung structure for lung cancer monitoring. Furthermore, in [128], homotopic mapping was adopted in an iterative Tikhonov regularization scheme, along with a Krylov subspace-based projection to improve both spatial and temporal resolution. Finally, in [129], a direct Landweber approach is used for two-phase flow electrical resistivity imaging in a phantom with acrylic rods.…”
Section: Tikhonov and L 2 -Norm Regularizationmentioning
confidence: 99%
“…In [127], the prior regularization filter was modified to incorporate a priori knowledge of lung structure for lung cancer monitoring. Furthermore, in [128], homotopic mapping was adopted in an iterative Tikhonov regularization scheme, along with a Krylov subspace-based projection to improve both spatial and temporal resolution. Finally, in [129], a direct Landweber approach is used for two-phase flow electrical resistivity imaging in a phantom with acrylic rods.…”
Section: Tikhonov and L 2 -Norm Regularizationmentioning
confidence: 99%
“…Meanwhile, the noise in measurement also causes randomness of the data. Previous researches have indicated that regularization is an effective way to alleviate these problems [13][14][15][16][17]. By incorporating the measurement data and a priori information, a reasonable solution consistent with both the data and the a priori knowledge can be obtained.…”
Section: Introductionmentioning
confidence: 99%